World Environmental and Water Resources Congress 2011 2011
DOI: 10.1061/41173(414)448
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Biodegradation Kinetics in an Anaerobic Batch Reactor

Abstract: Biodegradation of phenol with mixed consortia of bacterial was studied in an anaerobic batch reactor. The culture was acclimatized for a period of two months to grow in mineral salt medium contained phenol as the sole carbon source. Minimum and maximum concentrations of 50 and 1000 mg/l of phenol in the medium were used for the purpose of culture adaptation. The goals of these experiments were to determine the kinetics of biodegradation by determination of biomass growth rates and phenol concentrations with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…As phenol is toxic, the unrecovered activity could be attributed to its inhibition. This was consistent with previous studies, which reported 400 -600 mg/L phenol was the inhibitory threshold (Firozjaee et al 2011, Rosenkranz et al 2013). Nevertheless, CM groups still performed better.…”
Section: Experimental Setup and Operationsupporting
confidence: 94%
“…As phenol is toxic, the unrecovered activity could be attributed to its inhibition. This was consistent with previous studies, which reported 400 -600 mg/L phenol was the inhibitory threshold (Firozjaee et al 2011, Rosenkranz et al 2013). Nevertheless, CM groups still performed better.…”
Section: Experimental Setup and Operationsupporting
confidence: 94%
“…The value of K s (half-saturation coefficient) shows the affinity of the microorganism to the substrate. K s being inversely related to affinity of microbial system for substrate, a higher K s value indicates its lower affinity to the substrate (Firozjaee et al 2011). The value of K I (substrate inhibition constant) denotes the resistance of microorganism to the toxic effect of the substrate (Sahoo et al 2011).…”
Section: Biomass Growth Phenol Degradation and Growth Kinetic Modelingmentioning
confidence: 99%
“…Present as pollutants in many industrial wastewaters, the phenolics are responsible for chemical oxygen demand, odor, and toxicity (Hsien and Lin 2005;Juang and Tsai 2006;Firozjaee et al 2011;Holopainen et al 2013). Present as pollutants in many industrial wastewaters, the phenolics are responsible for chemical oxygen demand, odor, and toxicity (Hsien and Lin 2005;Juang and Tsai 2006;Firozjaee et al 2011;Holopainen et al 2013).…”
Section: Introductionmentioning
confidence: 99%